Women in Decision-Making and Peace Processes (Examples from the Kipchak Mongols) (Journal of the College of Basic Education, 2026)
Mongolian women in the Golden Horde of Fayhaq society enjoyed their full rights. They played a major role in peacemaking decisions , as well as their a ctive participation in most of the sultanh's decisions. They even assumed the throne at certain times from behind the scenes , and intervened in the decision to install the sultans . They often nominated their sons for power in a greement with the Mongol Princes. The queens also owned a lot of Private Property , contributed to trade , and sponsored councils of scholars therein.